Чингене — жертвы Холокоста? Нацистская политика в Крыму в отношении цыган, 1941–1944 - Тяглый, М. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article explores Nazi policies towards Gypsy population in the Crimea in 1941–44. Using comparative approach and trying to analyze Nazi decision-making process on «Gypsy problem » against a background of wider complex of wartime factors and events that played significant role in the Crimea (in particular, Nazi genocide of Jews) the author comes to the conclusion that, unlike the anti-Jewish policy (which had been already formulated by the Nazis in the course of their advance to the Crimean peninsula), the anti-Gypsy one was more subject to the influence and perceptions by the local Wehrmacht and SS authorities right on the spot. The profile of the Gypsy community in the Crimea with its strong interrelations to the Crimean Tatar population, and the argues by the latter to the Nazis for the former resulted in Nazi’s canceling of the genocidal policy; this demonstrates the absence of a universal ideological basis for the anti-Gypsy measures on the peninsula in particularly sharp relief and therefore does not allow to equal Nazi anti-Jewish policy with that on «Gypsy problem».